Greenfield approach to the reference network benchmarking methodology for performance-based regulation of distribution utilities - Ong Pe, Warren John B. (Quezon City College of Engineering, University of the Philippines Diliman, 2011)
Distribution systems are inherent monopolies and have generally been regulated to protect customers and to ensure cost-effective operation. From the traditional cost-of service regulation, global trend has been to move to performance-based regulation where utilities are compensated or penalized based on defined standards of performance. The study proposes a benchmarking methodology for the performance-based regulation of electric distribution utility using the greenfield service area approach to the reference network concept. In the greenfield approach, the reference network is built without consideration of the actual network, thus optimizing network topology. The reference network is established by determining the least cost spanning tree as a result of the optimization of the conductor as well as the reliability costs. Thus, to assess performance, the reference or optimized network serves as an objective benchmark and comparison to the actual network. The developed methodology has been tested against published test systems and has shown accurate results compared to other methods. The methodology was also applied to an actual MV system to determine and assess performance and viability particularly in the Philippine setting. The developed methodology produced lower total network cost compared to the actual network cost using the incremental approach.
Thesis (M.S. Electrical Engineering) - University of the Philippines, Diliman.
Keywords: Electric power distribution; Greenfield planning approach; Reference networks; Greenfield reference network; Electric power industry; Network optimization